Divulgação científica na Revista Ciência Hoje das crianças - Silveira, Marlise Almeida da (2010)
This research deals with the magazine Ciência Hoje das Crianças, edited by the Sociedade Brasileira para o Progresso da Ciência (SBPC), and brings into question the specificities of the language used by the magazine to scientific dissemination. The used sample is compound by the editions published in the year of 2008. The objective of this research is to identify the resources used by the magazine to fit the scientific language for the colloquial language, accessible to the lay public. The methodology used for the development of this research has qualitative bias and takes the resources of bibliographical research, interviews and discourse analysis of the French School. It appears that the magazine seeks to contemplate with its articles all areas of knowledge, which enables the reader to enlarge the view of the scientific world. For construction of the message in plain language, we identify that the magazine makes use of drawings, pictures, colors, typography, metaphors, analogies and textual structure organized primarily in narrative form